The Effect of Competency and Organizational Support on Employee Performance Mediated by Career Development at Hospital X - Fuji Hartati; Singmin Johanes Lo (Publikasi Indonesia, 2025)
In a competitive healthcare industry, employee performance is the main determinant of service quality. Hospital X, as a private hospital, faces challenges in maintaining the optimal performance of its nurses. Organizational competence and support are thought to strongly influence performance, with career development as a potential mediating factor. This research aims to investigate the factors that influence employee performance with a focus on competence, organizational support, and career development at Hospital X. The research population consisted of 104 permanent employees from the Nursing Department. Data analysis was conducted using the Structural Equation Model Partial Least Square (SEM-PLS). The results show that competence has a significant positive effect on employee performance and career development. Likewise, organizational support significantly influences both employee performance and career development. Career development is found to have a strong and positive impact on employee performance. Moreover, career development significantly mediates the relationship between competence and employee performance, as well as the relationship between organizational support and employee performance. These findings suggest that enhancing employee competence and providing organizational support, along with facilitating career development, are critical strategies to improve employee performance.